1983
DOI: 10.2220/biomedres.4.567
|View full text |Cite
|
Sign up to set email alerts
|

<b>PIT CELLS AS NATURAL KILLER </b><b>CELLS </b>

Abstract: The pit cells are one of the constituent cell types of the liver and are characterized by their characteristic granules and 'rod-cored vesicles.' In previous studies (7), we demonstrated their existence in the liver, spleen, and peripheral blood of rats, and described their close relationship with lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In fact, pit cells were described morphologically as a distinct cell type [ 11 before the concept of NK-cells and their correlation with LGL was well-established. It was previously suggested on the basis of morphologic similarities that pit cells correspond to LGL [4] and have a similar organ distribution as reported for NK cells in the rat [21]. We want to support this view with the present study: the pit cell should be regarded as the tissue equivalent of LGL.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In fact, pit cells were described morphologically as a distinct cell type [ 11 before the concept of NK-cells and their correlation with LGL was well-established. It was previously suggested on the basis of morphologic similarities that pit cells correspond to LGL [4] and have a similar organ distribution as reported for NK cells in the rat [21]. We want to support this view with the present study: the pit cell should be regarded as the tissue equivalent of LGL.…”
Section: Discussionsupporting
confidence: 82%
“…Later studies confirmed these observations [2, 31 but the function of this cell type remained unknown. In 1983, however, it was proposed that pit cells from rat blood may represent the electron microscopic (EM) description of large granular lymphocytes (LGL) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Their name was given because of the resemblance of their specific electron-dense granules with fruit pips (or "pits"). The function of these pit cells, however, was long unknown until Kaneda et al [13] proposed that they could represent NK cells. We recently reported that isolated and purified hepatic pit cells indeed have NK activity against YAC-1 tumor cells, and showed that pit cells are the electron microscopic equivalent of LGL (the latter being characterized by the presence of azurophilic granules in light microscopy) [l].…”
Section: Discussionmentioning
confidence: 99%
“…This ensures an instantaneous and simultaneous fixation preserving the shape, topography and ultrastructure of all cells and sinusoids. Owing to this technique, endothelial (Wisse 1972), Kupffer (Wake 1980;Wisse 1974), stellate (Wake 1980) and pit cells (liver resident NK cells) (Kaneda et al 1983;Wisse et al 1976) were characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this technique, endothelial (Wisse 1972 ), Kupffer (Wake 1980 ; Wisse 1974 ), stellate (Wake 1980 ) and pit cells (liver resident NK cells) (Kaneda et al. 1983 ; Wisse et al. 1976 ) were characterized.…”
Section: Introductionmentioning
confidence: 99%